Delayed-onset urticaria following vaccination for COVID-19 - Brandon L Clark; Brad A Yentzer (Wolters Kluwer Medknow Publications, 2022)
Background: As COVID-19 vaccines continue to be administered worldwide, there are an increasing number of studies documenting cutaneous reactions following vaccination. Systemic reactions, such as urticarial diseases, occur. Purpose: The main objective of this study was to investigate the association between urticaria and recent vaccination for COVID-19. Methods: A retrospective chart review examining the association of urticaria and COVID vaccination was conducted. Results: We report 17 patients who developed an urticarial reaction following vaccination against COVID and one patient who developed an urticarial reaction following a COVID infection. The vast majority of the patients were women with a mean age of 42.8 years. Conclusion: Cutaneous manifestations often follow COVID vaccination and infection. It may be helpful to inquire about recent infections and vaccinations in patients presenting with urticarial diseases.